2017
DOI: 10.18632/oncotarget.21828
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor activation contributes to RNF146 expression and neuroprotection in Parkinson's disease models

Abstract: RNF146 is an E3 ubiquitin ligase that specifically recognizes and polyubiquitinates poly (ADP-ribose) (PAR)-conjugated substrates for proteasomal degradation. RNF146 has been shown to be neuroprotective against PAR polymerase-1 (PARP1)-induced cell death during stroke. Here we report that RNF146 expression and RNF146 inducers can prevent cell death elicited by Parkinson’s disease (PD)-associated and PARP1-activating stimuli. In SH-SY5Y cells, RNF146 expression conferred resistance to toxic stimuli that lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Similarly, CRISPR-Cas9–mediated ERβ ablation eliminated the LG-induced neuroprotection against H 2 O 2 toxicity. Taken together, these data indicate that LG-induced activations of ERβ and RNF146 inhibit PARP1 and confer neuroprotection ( Kim et al, 2017 ).…”
Section: Pharmacological Activities Against Nddsmentioning
confidence: 84%
See 3 more Smart Citations
“…Similarly, CRISPR-Cas9–mediated ERβ ablation eliminated the LG-induced neuroprotection against H 2 O 2 toxicity. Taken together, these data indicate that LG-induced activations of ERβ and RNF146 inhibit PARP1 and confer neuroprotection ( Kim et al, 2017 ).…”
Section: Pharmacological Activities Against Nddsmentioning
confidence: 84%
“…Tamoxifen, an ER antagonist, blocked the LG-induced increase in RNF146 expression, indicating that ER activation was responsible for RNF146 induction. In addition, LG failed to induce RNF146 expression in an ERβ deletion model ( Kim et al, 2017 ).…”
Section: Pharmacological Activities Against Nddsmentioning
confidence: 98%
See 2 more Smart Citations
“…Interestingly, accumulating evidence has identified that AIMPs participate in various physiological and pathological processes as multifaceted molecules 10 13 . It was reported that the downregulation of AIMP1 enhanced transforming growth factor-β (TGF-β) signal by inducing the phosphorylation of Smad family member 2/3 (Smad2/3), which in turn promoted the chondrogenic potential of dedifferentiated/degenerated chondrocytes 14 .…”
Section: Introductionmentioning
confidence: 99%